2021
DOI: 10.1186/s12944-021-01434-8
|View full text |Cite
|
Sign up to set email alerts
|

Pemafibrate decreases triglycerides and small, dense LDL, but increases LDL-C depending on baseline triglycerides and LDL-C in type 2 diabetes patients with hypertriglyceridemia: an observational study

Abstract: Background Pemafibrate, a selective PPARα modulator, has the beneficial effects on serum triglycerides (TGs) and very low density lipoprotein (VLDL), especially in patients with diabetes mellitus or metabolic syndrome. However, its effect on the low density lipoprotein cholesterol (LDL-C) levels is still undefined. LDL-C increased in some cases together with a decrease in TGs, and the profile of lipids, especially LDL-C, during pemafibrate administration was evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
5
16
0
Order By: Relevance
“…Pema; pemafibrate, UC; unilateral common carotid artery occlusion, TG; triglyceride, TC; total cholesterol. Next, triglyceride (TG) and total cholesterol (TC) levels in the serum were examined (Figure 6B,C), as TG and TC levels have also been reported to be changed by administration of pemafibrate in various experimental models and clinical studies [31,[43][44][45]. Expectedly, we detected continuous decreases in serum TG levels and increases in serum TC levels in pemafibrate-administered UCCAO-operated mice in comparison with PBS-administered UCCAO-operated mice.…”
Section: Observation Of Retinal Thickness Changes By Pemafibrate Administration In a Mouse Model Of Uccao-induced Retinal Ischemiamentioning
confidence: 62%
“…Pema; pemafibrate, UC; unilateral common carotid artery occlusion, TG; triglyceride, TC; total cholesterol. Next, triglyceride (TG) and total cholesterol (TC) levels in the serum were examined (Figure 6B,C), as TG and TC levels have also been reported to be changed by administration of pemafibrate in various experimental models and clinical studies [31,[43][44][45]. Expectedly, we detected continuous decreases in serum TG levels and increases in serum TC levels in pemafibrate-administered UCCAO-operated mice in comparison with PBS-administered UCCAO-operated mice.…”
Section: Observation Of Retinal Thickness Changes By Pemafibrate Administration In a Mouse Model Of Uccao-induced Retinal Ischemiamentioning
confidence: 62%
“…In our previous study, it was found that type 2 diabetes patients with hypertriglyceridemia can be divided into two groups: those with relatively low LDL-C and those with normal or high LDL-C. In the former group, TGs and sd-LDL were also higher than those in the latter group, but there was no difference in non-HDL-C between the two groups (4.9 [4.0-5.4] mmol/L vs. 4.8 [4.5-5.2] mmol/L) [9]. Alternatively, the increase in TGs and decrease in LDL-C (calculated using Friedewald's formula) could have been synchronized [13,32], and the change in non-HDL-C might have been offset.…”
Section: Discussionmentioning
confidence: 92%
“…If so, calculated non-HDL-C, regardless of the LDL-C assay method used, will largely re ect the decline in buoyant LDL present in some type 2 diabetes patients, and it is estimated that the increase in non-HDL-C would not be as expected. The changes in LDL composition would affect the measurement of non-HDL-C and thus impair its clinical reliability, and these changes might also affect the relationship between non-HDL-C and sd-LDL [9]. In contrast, another lipid marker that indirectly compares the changes in sd-LDL and buoyant LDL (i.e., the TG/LDL-C ratio) seems to more accurately re ect the pathophysiology of dyslipidemia in type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations